Electromagnetic Anomalies around The Wenchuan Earthquake and Their Relationship with Earthquake Preparation - Xuemin Zhang; Xuhui Shen (International Journal of Geophysics)
Electromagnetic precursors before the Wenchuan earthquake on May 12, 2008 were collected and summarized on the basis of related published papers. The relationship between electromagnetic anomalies and different earthquake preparation stages was analyzed, and an entire seismic preparation process was constructed according to corresponding anomalies in different electromagnetic parameters. It is illustrated that stereo electromagnetic observation is useful in the understanding of earthquake preparation mechanism. It is inevitable that a lot of problems exist in anomaly distinguishing and coupling mechanism analysis, which needs further studies in future.